2015
DOI: 10.11622/smedj.2015139
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of intratesticular leiomyoma

Abstract: A 47-year-old man presented with a scrotal swelling. Ultrasonography of the testes showed that it was an extratesticular swelling. However, the swelling was intraoperatively found to be intratesticular. Histology showed an intratesticular leiomyoma, which is extremely rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…On microscopy, they are seen to be well-circumscribed lesions composed of interlacing bundles of smooth muscle cells. [15] In the present study, we reported a case of intratesticular leiomyoma which, on gross examination, measured 10.5 x 9 x 7.5 cm and microscopically, was composed of loose fascicles of spindle cells with vesicular uniform nuclei in a hyalinized stroma. These tumours are exceptionally rare.…”
Section: Discussionmentioning
confidence: 66%
“…On microscopy, they are seen to be well-circumscribed lesions composed of interlacing bundles of smooth muscle cells. [15] In the present study, we reported a case of intratesticular leiomyoma which, on gross examination, measured 10.5 x 9 x 7.5 cm and microscopically, was composed of loose fascicles of spindle cells with vesicular uniform nuclei in a hyalinized stroma. These tumours are exceptionally rare.…”
Section: Discussionmentioning
confidence: 66%
“…Rare benign solid lesions located on the testis include epidermoid cyst, Leyding cell hyperplasia, gonadal stroma originated fibroma, hemangioma, leiomyoma, spontaneous hemorrhages, sarcoidosis and tuberculosis [1]. Leiomyomas located in the testis are extremely rare.…”
Section: Discussionmentioning
confidence: 99%
“…They may originate from the smooth muscle cells of vessels as well as totipotent teratomas [6]. According to another opinion, they originate from the tunica propria of seminiferous tubules or smooth muscle cells of the tunica albuginea [1]. On macroscopic evaluation, they are well-defined, having a whorled cut surface [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations